PENERAPAN SISTEM KENDALI KELISTRIKAN PADA GRID PLTS-PLN MENGGUNAKAN PLC OUTSEAL - Risaldi Rajab (Joule (Journal of Electrical Engineering), 2024)
Solar power plant (PLTS) is a new renewable energy that currently many people are starting to develop it because PLTS is an environmentally friendly generator and does not use fossil energy so as to protect its availability. Solar power plants produce energy using photovoltaic which converts solar radiation into electrical energy in the form of direct current or direct current (DC) which is then converted into alternating electric current using an inverter. The PLTS system is divided into two, namely the on-grid system and the off-grid system. The on-grid system is a system that only produces power when the PLN network is available and the use of batteries on mini-sites is not mandatory. While the off grid system is a system that stores PLTS power in the battery for use when the PLN network is unavailable or dead. So the purpose of this research is to build a system that is connected to PLN and battery with the automatic function of moving resources in the off grid system by conducting some experiments and discussions with simple PV mini-grid practitioners who are currently experiencing some problems when operating the power switch which is still operated manually. So this research was made to build an automation system that connects PLN and PLTS resources which are the main resources automatically so that it is more practical to use. Solar power plant (PLTS) is a new renewable energy that currently many people are starting to develop it because PLTS is an environmentally friendly generator and does not use fossil energy so as to protect its availability. Solar power plants produce energy using photovoltaic which converts solar radiation into electrical energy in the form of direct current or direct current (DC) which is then converted into alternating electric current using an inverter. The PLTS system is divided into two, namely the on-grid system and the off-grid system. The on-grid system is a system that only produces power when the PLN network is available and the use of batteries on mini-sites is not mandatory. While the off grid system is a system that stores PLTS power in the battery for use when the PLN network is unavailable or dead. So the purpose of this research is to build a system that is connected to PLN and battery with the automatic function of moving resources in the off grid system by conducting some experiments and discussions with simple PV mini-grid practitioners who are currently experiencing some problems when operating the power switch which is still operated manually. So this research was made to build an automation system that connects PLN and PLTS resources which are the main resources automatically so that it is more practical to use.